Role of Community Forestry in Farmers Welfare Improvement at District Ngarip Tanggamus - Susni Herawati (Politeknik Negeri Lampung, 2013)
Poverty is one of the social economicÂ problem in the world that influence stability of the country in multi sector. In Indonesia, poverty level reach about 14% and 63% is in rural area. Ministry of forestry has important role to improve forestry sector through their program which called community forestry as one of schemes of forest management based on community. This study aims to identify role of community forestry to increase human welfare, to analyse life worth living and land area needed. This research was conducted in Desa Ngarip, Lampung Province for 2 months. Data were analyzed by quantitative and descriptive method. The result showed that community forestry had high contribution. It was 53%Â to total income. Based on life worth living analysis, the highest cost wasÂ basic necessities and it attempted to 60% to total cost. If compared with profit level of farmer, land area needed was 1,8 hectare to meet farmer requirements.Keywords: role of community forestry, life worth living